Herpes zoster ophthalmicus with retrobulbar neuritis - Singh, Pranisha; Karmacharya, Srijana; Rizyal, Aparna; Rijal, A P (Nepalese Journal of Ophthalmology, 2016)
Background: Retrobulbar neuritis in Herpes Zoster Ophthalmicus (HZO) has been reported very rarely. Objective: To report a very rare case of HZO with retrobulbar neuritis with detailed clinical features and treatment responses. Case: A fifty-eight- year old male presented with Herpes zoster-retrobulbarneuritis in the left eye. It was characterized by decreased visual acuity, mid dilated pupil with sluggish reaction, normal optic disc and central scotoma in Humphrey visual field. Visual acuity improved with systemic Acyclovir and steroids. Conclusion: This is a rare case of HZO associated with retrobulbar neuritis. Prompt treatment with systemic antiviral and steroid improve the visual outcome. Nepal J Ophthalmol 2016; 8(15): 78-81